The Influence of Social Media, Marketplaces, and Influencers on Increasing Culinary MSME Sales in Cilacap City - Nurlasih, Finda; Nurwibowo, Fajar; Mubarak, Zulfikar Yusya (Universitas Mohammad Husni Thamrin, 2025)
Advances in digital technology have driven significant changes in the marketing strategies of Micro, Small, and Medium Enterprises (MSMEs), particularly in the culinary sector. Digitalization has driven changes in consumer behavior in seeking information, comparing products, and making purchases. Consumers are now increasingly influenced by digital media, such as social media, marketplaces, and influencer recommendations. The use of social media, marketplaces, and influencers has become a key tool for increasing market reach and sales. Social media, particularly Instagram, has become an effective promotional tool due to its ability to display product visuals attractively. This study aims to analyze the influence of social media, marketplaces (GoFood), and influencers on increasing sales of culinary MSMEs in Cilacap City. The research method used is quantitative research with an explanatory approach. The research sample consisted of 100 culinary MSMEs, determined using a purposive sampling technique. Data collection was conducted through a questionnaire with a Likert scale and analyzed using multiple linear regression with the help of SPSS. The results show that social media and marketplaces have a positive and significant effect on increasing sales of culinary MSMEs, while influencers have a positive but insignificant effect. Simultaneously, social media, marketplaces, and influencers significantly influence sales growth for culinary MSMEs in Cilacap City. This study recommends optimizing the use of social media and marketplaces as primary digital marketing strategies for culinary MSMEs.